Addi Akaweh, Tigray, Ethiopia. Archaeological rescue excavations at the site of Abunä Gärima in Wuqro (Tigray, Ethiopia). Season 2017 - Pfeiffer, Kristina; Reichmuth, Silvio; Lienig, Adrian; Hamel, Hanna (e-Forschungsberichte des DAI, 2018)
The 2017 season was undertaken in early spring 2017. It included excavations at the church of Abunä Gärima (AG) in Addi Akaweh, as well as consolidation activities of the church walls. The main focus for the season was set on the church of Abunä Gärima as being part of a rescue excavation which aimed to study the possibility to consolidate the walls to avoid further wall cracks. The excavation was further associated with research regarding the potential of being an Ethio-Sabaean cultic site.